Studying of tense and aspect verb categories on Ukrainian as foreign language lessons for the first-year students (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with the methods of study tense verb forms of perfect and imperfect aspects on Ukrainian lessons with first-year foreign students of all specialties. The kinds of exercises for actualization, intensification, systematization, generalization, consolidation of foreign students’ knowledge about tense and aspect verb categories are proposed.
Keywords: verb; infinitive; perfect aspect; imperfect aspect; tense of verb